Anticancer and antibacterial potential of Rhus punjabensis and CuO nanoparticles. Issue 5 (3rd March 2020) - Naz, Sania; Tabassum, Saira; Freitas Fernandes, Nelson; Mujahid, Mohammad; Zia, Muhammad; Carcache de Blanco, Esperanza J.
Abstract: The present study reports ecofriendly synthesis of CuO nanoparticles (NPs) using an extract of Rhus punjabensis as a reducing agent. NPs structural and composition analysis are evaluated by X-rays diffraction (XRD), Fourier transform infrared, Energy dispersive spectroscopy, Scanning electron microscopy, Transmission electron microscopy, and Thermal analysis. The NPs have pure single phase monoclinic geometry with spherical structure and high stability toward heat and with average particle size of about 36.6 and 31.27 nm calculated by XRD and SEM, respectively. NPs are tested for antibacterial, protein kinase (PK) inhibition, SRB cytotoxic, and NF-κB activities. Antibacterial activity is observed against B. subtilis and E. coli . Significant PK and SRB cytotoxic activity is observed with some NF-κB inhibition. NPs IC50 values against HL-60 and PC-3 prostate cancer cells are 1.82 ± 1.22 and 19.25 ± 1.55 μg/mL. The results encourage further studies for antibacterial and anticancer drug development of NPs using animal models. Abstract :